PENGARUH GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2019 - 2023) - Sugalih, Muhamad; Yuliana Priska (Publika Citra Media, 2025)
This study aims to test and obtain empirical evidence regarding the influence of institutional ownership, independent commissioners, audit committees, managerial ownership, and Corporate Social Responsibility on Tax Avoidance. This study uses a sample of Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023 with a population of 125 companies. The method for determining the sample for this study uses a purposive sampling method, obtained 12 company samples with an observation period of 5 years obtained data of 60 research data. The type of research in this study is quantitative research. The analysis technique used is panel data regression processed using Eviews software version 10. The results of this study indicate that partially Institutional Ownership has no significant effect on Tax Avoidance (2) Independent Commissioners have no significant effect on Tax Avoidance (3) Audit Committee has a significant effect on Tax Avoidance, (4) Managerial Ownership has no significant effect on Tax Avoidance, and (5) Corporate Social Responsibility has no significant effect on Tax Avoidance